LENGUAS DE COMPÁS ACENTUAL Y LENGUAS DE COMPÁS SILÁBICO. REVISIÓN TEÓRICA E IMPLICACIONES PEDAGÓGICAS - Cuenca Villarín, María Heliodora (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In this paper the traditional rhythmic classification of stress-timed and syllable-timed languages has been revised by means of the analysis of syllable structure, vowel reduction, intersyllabic compression and the strength of the contrast between stressed and unstressed syllables in an English and Spanish global corpus consisting of carrier sentences, read prose and oral samples of spontaneous speech. Obviously, this theoretical revision involves a pedagogical shift from pyramidal exercises devised to achieve isochronous interstress intervals in English to activities focussed on duration differences between stressed and unstressed syllables.